2020
DOI: 10.1002/sd.2083
|View full text |Cite
|
Sign up to set email alerts
|

CO2 emissions and sustainable economic development: New evidence on the role of human capital

Abstract: The empirical literature testing the Environmental Kuznets Curve hypothesis reports mixed results on the existence of this relationship. This study argues that the effects of economic development on CO 2 emissions are contingent upon the level of human capital. In the beginning, when human capital starts increasing from its low levels, more education accelerates the use of non-renewable resources and increases pollution emissions. However, when certain threshold levels of schooling are traversed, further enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 55 publications
9
64
0
1
Order By: Relevance
“…However there are also some other potential solutions which are helpful in eradication of carbon emissions. For instance, findings reported by Khan et al (2020) suggested the use of renewable energy, investing in human capital (Khan, 2020), and preservation of natural resources (Zafar, Saeed, Zaidi, & Waheed, 2020) in the gradual eradication of the levels of carbon emissions whereas technological innovation can also served for the said purpose (Ulucak & Khan, 2020). Besides being a cost bearing investment, sustainable logistics also helps firms to have increased profits (Prajogo, Chowdhury, Yeung, & Cheng, 2012) whereas it will also strengthen the market reputation of the firms ethically, morally and financially (Porter & Van der Linde 1995).…”
Section: Logistics Performance and Environmentmentioning
confidence: 99%
“…However there are also some other potential solutions which are helpful in eradication of carbon emissions. For instance, findings reported by Khan et al (2020) suggested the use of renewable energy, investing in human capital (Khan, 2020), and preservation of natural resources (Zafar, Saeed, Zaidi, & Waheed, 2020) in the gradual eradication of the levels of carbon emissions whereas technological innovation can also served for the said purpose (Ulucak & Khan, 2020). Besides being a cost bearing investment, sustainable logistics also helps firms to have increased profits (Prajogo, Chowdhury, Yeung, & Cheng, 2012) whereas it will also strengthen the market reputation of the firms ethically, morally and financially (Porter & Van der Linde 1995).…”
Section: Logistics Performance and Environmentmentioning
confidence: 99%
“…They found that there are substitutability relationships between human capital and energy utilization. Khan [21] argued that the influence of economic development on emissions is dependent upon the human capital level, after a certain level of human capital, CO 2 emissions will be reduced, and environmental awareness and friendly technologies will be promoted. Hao et al [22] specially investigated the effects of human capital on CO 2 emissions for G7 countries for the period 1991-2017 and discovered that human capital can reduce CO 2 emissions.…”
Section: Innovative Human Capital and Co 2 Emissions Nexusmentioning
confidence: 99%
“…The unfavorable influence of FFUEL on the green practices of RENG implies that an enhance in the utilization of fossil fuels, and related energy is directly linked with the decline in the RENG. According to Godil, Sharif, Agha, and Jermsittiparsert (2020); Godil, Sharif, Afshan, Yousuf, andKhan (2020) andBektas ¸, Demir, and Laporte (2016), heavy taxes need to be imposed on the vehicles to minimize their usage and ultimately discourage the increased utilization of FFUEL associated activities, and therefore enhancing the indicators of a green environment.The outcomes of this endeavor are quite in line with other endeavors and hence validate the results stated in the researches carried out previously on the utilization of eco-friendly energy sources and their crucial influence on the health of individuals and the economy(Benitez, LIorens, & Fernandez, 2015; S. A. R Khan et al, 2018;.…”
mentioning
confidence: 99%